Penerapan Strategi Model 7S McKinsey (Studi pada Sekolah Tinggi Ilmu Ekonomi Swadaya) - Alfu Fauzan; Winaya Purwanti (Cakrawala Akuntansi & Manajemen, 2023)
This research is an application of the 7S Mckinsey model on the STIE Swadaya campus how the organizational culture conditions are for improving performance at STIE Swadaya, identifying obstacles to existing strategy implementation on campus, suggesting improvements that need to be made in implementing the strategy. The research method uses a qualitative-descriptive approach by giving questionnaires to 30 lecturers and staff of STIE Swadaya. This research program examines the application of the 7s McKinsey Framework in the assessment aspect, namely the field of human resources (HR). The results of this study found that there were differences in quantitative and qualitative assessments in the field of human resources (HR) at STIE Swadaya which indicated that there were still obstacles in managing human resource management at STIE Swadaya seen in the application of the 7s McKinsey Framework.Key Words : Strategy application, 7s McKinsey Framework